Mouth-to-mouth, pocket mask, or i-gel® resuscitation on a moving rescue boat: How do different ventilation methods affect CPR? A pilot study - Carracedo-Rodríguez, Eloy; Webber, Jonathon; Fernández-Méndez, María; Otero-Agra, Martín; Alonso-Calvete, Alejandra; Barcala-Furelos, Roberto (The American journal of emergency medicine, 2025)
The use of Inflatable Rescue Boats (IRBs) for cardiopulmonary resuscitation (CPR) in aquatic environments presents unique challenges due to their inherent instability and technical limitations. Despite the critical role of effective ventilation in cardiac arrest, there is a significant knowledge gap regarding optimal strategies to achieve this on IRBs. To compare the effectiveness of three ventilation methods—Mouth-to-Mouth (MM), Pocket Mask (PM), and i-gel® supraglottic airway device (IG)—in initiating CPR on a moving IRB. A randomized crossover pilot study was conducted with 16 trained lifeguards. Each participant performed CPR using the three ventilation methods on a resuscitation manikin with the IRB under power (cruising) at 20 knots. The study measured the time to initiate CPR and resuscitation skills, including ventilations and chest compressions. The MM method resulted in the shortest time to initiate CPR, with a median of 4 s, compared to PM and IG, which had medians of 8 and 14 s, respectively. IG was significantly later in initiating ventilation compared to MM (p < 0.001) and IG (p = 0.006). No significant differences were observed in the number of effective ventilations or average ventilation volume among the methods (p > 0.05). Simple strategies such as MM or PM provide ventilations that are just as effective as those using IG in manikins and allow for faster initiation of CPR while under power in an IRB.